Analisis Anggaran Biaya Produksi Sebagai Alat Pengendalian Biaya Pada Perusahaan Daearah Air Minum (PDAM) Kota Kupang - Reu, Fransiskus Marlon (P3M- Politeknik Negeri Kupang, 2022)
The problem raised in this research is how the procedure for preparing the production cost budget and the process of controlling production costs in PDAM Kupang Regency. The purpose of this study was to find out the procedure of preparing the production cost budget and for the process of controlling production costs at the kupang district drinking water company. The method used in this research is descriptive qualitative. The results showed that the calculation of production costs in PDAM Tirta Lontar Kupang Regency has not been in accordance with the theory and process of water production in PDAM Tirta Lontar Kupang Regency has always increased.